Political Theory and Foundations of Royal Power in the Viceroyalty of Peru (XVI-XIX) - Morales Cerón, Carlos (2010)
The present work of impracticalness, you have for purpose, explaining the basics of the power practiced during the colonial Peru unraveling the theoretic basics they were with explained and rationalized. The logic of the imperial power and virreinal was rationalized principally by judges and essayists of the Spanish right and prominent exponents of the moral theology. Mention of the mechanisms used by the viceroys to be able to legitimate m before the marital status and priest and in front of the common people likewise becomes urban rural.